Literature review on shift work and nurse’s burnout - Reisinho, João (2022)
Abstract of communication presented at the Fourth International Congress of CiiEM: Health, Well-Being and Ageing in the 21st Century. Egas Moniz University Campus, Monte de Caparica, Portugal, 3–5 June 2019